PENCATATAN PERNIKAHAN SEBAGAI UPAYA PENANGGULANGAN NIKAH SIRRI DALAM HUKUM ISLAM (Analisis Terhadap Metode Penggalian Hukum) - Islamiyati Islamiyati (Masalah-Masalah Hukum, 2010)
Nikah sirri represent nuptials from conducted underhand or is not noted officially by state. Nikah sirri do not influence to legality of marry, because record keeping marry do not the inclusive of condition and foundation marry, along with opinion growth punish Islam really the nuptials record-keeping have very role is necessary happening of nuptials, releasedly of act marry serve the purpose of arm law when one of couple do not execute obligation. Although the nuptials record-keeping not yet been arranged in Islam Law, but to analysein perpective punish Islam needed by a dig method law (ijtihad) by moslem scholar, namely method Qiyas, Istihlah, al-Dzari'ah, Urf. Each regulation believed can uphold kindliness represent translating from Islam teaching values. Become according to ijtihad of moslem scholar have a nation that Nikah sirri law is illegal, and record keeping marry is obligation so that cause goodness at Islam people. According to contemporary moslem scholar have a notion that conducted better nuptials record-keeping is so that punished to marry validly according to religion and validate according to state.Kata Kunci : Nikah Sirri, Hukum Islam, Metode Penggalian Hukum.